HUBUNGAN RENTANG LENGAN DENGAN TINGGI BADAN DALAM MENENTUKAN INDEKS MASSA TUBUH LANSIA - Wati, Desti Ambar (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: As you get older, a person will experience a decrease in bone and muscle mass affecting bone structure changes. The process is said to be aging. Objective: The purpose of this research is to find out the corelation between hand range toward body height and in determining body mass index (BMI) of elderly in Distric Semarang. Method: This study used cross sectional design. Subjects of the study were the elderly in Kelurahan Candigaron Distric Semarang, which consisted of 60 people consisting of 30 men and 30 women. Sampling technique used is purposive random sampling. Height is measured using microtoise, weight using digital weight scales, and arm range using metline. The data obtained then tested the normality with Kolmogorov-Smirnov test which then continued with Rank Spearman correlation test. Results: Based on the analyzis of height and armspan by using Rank Spearman correlation test, the result was r = 0,921 (female) dan r = 0,819 (male). Whereas, Rank Spearman correlation test between BMI height (BMI TB) and BMI armspan (BMI RL) gave a result of r = 0,965 (female) and r = 0,905 (male). Significancy of the whole test was < 0,05. This result showed that there were strong, linear, and significant relation between armspan and height, along with BMI TB and BMI RL. Conclusion: Armspan is reliable as substitute height in determining body mass index of the elderly in Distric Semarang, because there is a strong and significant relation between height - armspan and BMI height - BMI arm span.